2018
DOI: 10.1002/jcb.26536
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of antioxidants in the management of neurodegenerative disorders: A literature review

Abstract: It is proven that oxidative stress has a pivotal role in the process of neurodegeneration. The use of antioxidants is an attractive method to prevent the incidence of neurodegenerative diseases. We searched major databases (PubMed, Med Line and Google Scholar) using the keywords of neurodegeneration, oxidative stress, and antioxidant for both review and original studies which have reported the various beneficial effects of antioxidants. About 70 studies were identified for this review. Among various antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…In addition, current knowledge on treating schizophrenia with antioxidants is presented, along with information on how antioxidant levels in patients with schizophrenia may be regulated by nutritional, pharmacological, and lifestyle factors. Because schizophrenia is a progressive disorder from its onset in adolescence or early adulthood [ 10 , 26 , 27 , 28 ], the intake of natural antioxidants may help regulate its development [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, current knowledge on treating schizophrenia with antioxidants is presented, along with information on how antioxidant levels in patients with schizophrenia may be regulated by nutritional, pharmacological, and lifestyle factors. Because schizophrenia is a progressive disorder from its onset in adolescence or early adulthood [ 10 , 26 , 27 , 28 ], the intake of natural antioxidants may help regulate its development [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morato et al have shown that some phenolic compounds of olive oil (oleocanthals and triterpene acids) have strong neuroprotective effects and, therefore, can serve as a therapeutic intervention in the treatment of NDs. Additionally, they have reported that the Mediterranean diet, which is usually rich in olive oil, is associated with a lower incidence of NDs [80,81].…”
Section: Interventionsmentioning
confidence: 99%
“…Weinreb et al have documented that the polyphenolic components of green tea, with a high antioxidant capacity, can function as neuroprotective agent and reduce the incidence of DNs. Following this line of research, it is suggested that the consumption of green tea can protect neurons from oxidative stress damage [80].…”
Section: Interventionsmentioning
confidence: 99%
“…Therefore, the study of paraquat in relation to Parkinson's disease is warranted [11]. The cellular mechanisms of protection against PQ toxicity include activation of antioxidant pathways and autophagy as well as overexpression of a heat shock proteins' machinery [12][13][14][15]. Thus, compounds that can trigger one or all of these strategies are of interest as cytoprotective agents.…”
Section: Introductionmentioning
confidence: 99%